Gasifikasi Cangkang Sawit dalam Updraft Fixed Bed Gasifier: Pengukuran Laju Gasifikasi Spesifik - Renardi Andhika; Herri Susanto (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Gasification is process conversion solid material into fuel gas. This study were carried on updraft fixed bedgasifier. Commercial application for updraft gasifier is used in Asphalt Mixing Plant at Ngawi with thecapacity 1 ton/hour. Palm shell was used as feedstock in this study with air as gasifying agent. Feedingconducted as batch and intermittent (0.5 kg every 12 minute in certain time). Gasification process alsoproduced an undesirable product called tar. The analysis of tar measurement and gas composition wasperformed by impinger bottle method and GC-TCD respectively. Gasification performance observed includesflare ignition, temperature progress, tar quantity, and specific gasification rate. Biomass with high moisturecontent produces producer gases that will be difficult to burnt because producer gases carried moisturecontent from biomass. Flare ignition on biomass with moisture content 7,01% would be slower 2 minutesthan moisture content 4%. Flammable producer gases when net calorific value more than 3500 kJ/Nm3.Temperature progress with intermittent feeding increase faster than batch feeding. However, temperaturprogress decreases when biomass was fed into the reactor. Tar content with high temperature on intermittentfeeding (4.8 mg/Nm3) was smaller than batch feeding (14 mg/Nm3). In this study, spesific gasification rate(SGR) about 47.7 - 65.4 kg/m2h.